Scrutinizing the Nanostructural and Nanomechanical Features of Regenerated Cellulose Ultrafiltration Membranes - Silva, Luciano Paulino (Journal of Membrane and Separation Technology, 2015)
Ultrafiltration (UF) membranes have been widely used for many separation processes in which high performance is required. Commercial regenerated cellulose UF membranes with variable molecular weight cut-offs were characterized by high performance atomic force microscopy (AFM) using the novel quantitative nanomechanical mapping mode and the versatility of its signal channels towards nanoscale features elucidation of the materials surface. In addition, Raman spectroscopy was applied in order to investigate some possible chemical behavior changes associated with the UF membranes’ cut-offs. Overall, the results showed that the proposed AFM method was reliable to gain qualitative and quantitative data at unprecedented nanoscale resolution and such information can be used to distinguish UF membranes according to their specific molecular weight cut-offs and properties even on situations in which the molecular behavior were not influenced by the UF membrane’ cut-off. This approach can be useful on quality control procedures of researchers and manufacturers producing or modifying these polymeric materials.